2016
DOI: 10.1213/ane.0000000000001503
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Neuromonitoring for Identification of New Neurologic Deficits in Pediatric Spinal Fusion Surgery

Abstract: TcMEPs are more sensitive than SSEP at detecting an impending NND. IONM modalities are highly specific. Both sensitivity and specificity are impacted substantially by assumptions of the impact of interventions on alerts and NND. Properly designed, controlled, multicenter studies are required to establish diagnostic accuracy of IONM in scoliosis surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…In conclusion TcMEPs may help detect and prevent new neurological deficits during spine surgery for scoliosis and other deformities. TcMEPs are easier to elicit, may detect changes earlier than SSEPs and are thought to be more sensitive in identifying spinal cord injury ( Neira et al, 2016 , Koht and Sloan, 2016 ). In our series of 61 INMs in 56 children, we assume that the INM alert and resultant surgical corrective action prevented new deficits in two children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion TcMEPs may help detect and prevent new neurological deficits during spine surgery for scoliosis and other deformities. TcMEPs are easier to elicit, may detect changes earlier than SSEPs and are thought to be more sensitive in identifying spinal cord injury ( Neira et al, 2016 , Koht and Sloan, 2016 ). In our series of 61 INMs in 56 children, we assume that the INM alert and resultant surgical corrective action prevented new deficits in two children.…”
Section: Discussionmentioning
confidence: 99%
“…The risk appears to be higher for those with pre-existing deficits, especially neurological, and those with multisystem involvement. Tailored intraoperative neuromonitoring (INM) with transcranial electrical motor evoked potentials (TcMEP), somatosensory evoked potentials (SSEP), free running electromyograms (EMG) and stimulus triggered EMG (Stim EMG) may mitigate the risk of permanent injury and adverse neurological outcomes during certain surgeries ( Cheng et al, 2014 , Lieberman et al, 2008 , Senkoylu et al, 2017 , Novais et al, 2017 , Neira et al, 2016 , Piasecki et al, 2018 , Purger et al, 2015 , Samdani et al, 2016 , Galloway and Zamel, 2011 , Pastorelli et al, 2015 , Jea, 2014 , Sala et al, 2010 , Nuwer et al, 2012b , Fehlings et al, 2010 , Langeloo et al, 2003 , McIntyre et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…39 TcMEPs are more sensitive than SSEP in estimating the risk of impending neurological deficits. 23,39 In a study evaluating the effect of IONM on outcomes of complex paediatric scoliosis surgeries, lower (but statistically insignificant) neurological complications were seen in the monitoring group as compared to no monitoring group. 40 Multicentric studies with a larger group of paediatric patients are needed to prove the accuracy of IONM in scoliosis surgery.…”
Section: Available Evidencementioning
confidence: 97%
“…4 A previous Canadian study from the Children's Hospital of Eastern Ontario reported positive and negative predictive values of 12% and 98.2%, respectively. 7 Nevertheless, almost all these studies were retrospective in nature and, most importantly, all these studies suffered from potential misclassification bias. 5 Misclassification bias may occur when a rescue intervention is typically employed in the event of the intraoperative identification of EP alert, therefore the rescue intervention (i.e., treatment) may alert the outcome before a reference test is applied (i.e., postoperative neurologic examination) in these studies.…”
mentioning
confidence: 99%
“…4 Une étude canadienne du Centre hospitalier pour enfants de l'est de l'Ontario avait fait état de valeurs prédictives positives et négatives de 12 et 98,2, respectivement. 7 La quasi totalité de ces études étaient toutefois de nature rétrospective et, surtout, elles souffraient toutes d'un biais potentiel de classification erronée. 5 Un biais de classification erronée peut survenir lorsqu'une intervention de sauvetage est généralement utilisée en cas d'identification peropératoire de l'alerte au niveau des PE; ainsi l'intervention de sauvetage (c.-à-d. le traitement) pourrait 'prévenir' le devenir avant l'application d'un test de référence (c.-à-d. un examen neurologique postopératoire) dans ces études.…”
unclassified